Closer than she knows - Irvin, Kelly (Thomas Nelson, 2020)
As a court reporter, Teagan O'Rourke has written official records for dozens of real-life murders. But she's never known the smell of death. Then a young police officer is murdered just inches away from her, and a man calling himself a serial killer starts leaving Teagan notes, signing each with the name of a different murderer from her favorite mystery novels. Teagan turns to her friend Max Kennedy. He longs for more than friendship with Teagan - and now he's wondering if he'll be able to keep Teagan alive long enough to find out if he has a chance. -- adapted from back cover